Pemberian Enzim Lignosellulosa dalam Pakan Buatan Terhadap Pertumbuhan dan Tingkat Kelulushidupan Benih Ikan Gurami (Osphronemus gouramy Lac.) [The Granting Of An Enzyme Lignosellulosa in Feed Artificial On The Growth and The Survival Rate Seed Gourami (Osphronemus gouramy Lac.) ] - Agustono Agustono; Muhammad Yusuf Akbar; Rahayu Kusdarwati (Jurnal Ilmiah Perikanan dan Kelautan, 2013)
Abstract Gurami having economic values of. Have abundance, namely able in waters with its oxygen relatively low. Belong to the species of carnivorous herbs herbivora. Unprofitableness is eat feed derived from herbs with content nutrition relatively low compared to animals, so it impact on its growth slow, easly diseases, easly stress, hard eat and SR low. The purpose of this research isto know the addition of enzyme lignosellulase in artificialfeedincreased growth and increased survival rate seed gourami. Method research used is experimental with delightful random complete (RAL) with five treatment and four deuterenomy. The treatment used were : control (A), enzyme 550ml (B), enzyme 600ml (C), enzyme 650ml (D), and enzyme 750ml(E). The main parameters measured were growth rate, and survival rate. The supporting parameters observedwas water quality. Data analysis used analysis of variance (ANOVA) to know the effect of the treatments.To know the difference among treatments used Duncan's Multiple Range Test (DMRT). The result showed that the provision of enzymes give a real power (p<0.01) against growth rate daily and growth long absolute gourami (Osphronemus gouramy) To survival rate and feed conversion ratio gourami give impact which is not dissimilar real. Growth best on treatment E (0.0214), then successive followed by treatment D (0.0174), C (0.015), B (0.0142) and A (0.0128). Conversion ratio feed on all treatment e 10,415, that is, e then successive followed by treatment d (12,915), c (14,3975), b (15,6375) and a (17,5325). Survival rate obtained 100%. Water quality media maintenance gourami is temperature 26ºC - 29ºC, pH 7 – 8, oxygen dissolved 3.5 – 5 mg/l and ammonia 0.004 – 0.005 mg/l.